2017
DOI: 10.1186/s12864-017-4345-7
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen exposure overrides the masculinizing effect of elevated temperature by a downregulation of the key genes implicated in sexual differentiation in a fish with mixed genetic and environmental sex determination

Abstract: BackgroundUnderstanding the consequences of thermal and chemical variations in aquatic habitats is of importance in a scenario of global change. In ecology, the sex ratio is a major population demographic parameter. So far, research that measured environmental perturbations on fish sex ratios has usually involved a few model species with a strong genetic basis of sex determination, and focused on the study of juvenile or adult gonads. However, the underlying mechanisms at the time of gender commitment are poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 82 publications
(94 reference statements)
1
12
0
Order By: Relevance
“…For example, Nile tilapia ( Oreochromis niloticus ) exposed to elevated temperature can override genetic sex determination, and the females can be reversed to produce pseudomales (Baroiller et al, 2009). Blue tilapia ( Oreochromis aureus ), Japanese flounder ( Paralichthys olivaceus ), European sea bass ( Dicentrarchus labrax ), turbot ( Scophthalmus maximus ) and Atlantic silverside ( Menidia menidia ) also undergo temperature induced ESR (Conover and Fleisher, 1986; Desprez and Mélard, 1998; Yamaguchi et al, 2007; Diaz and Piferrer, 2015; Robledo et al, 2015; Diaz and Piferrer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nile tilapia ( Oreochromis niloticus ) exposed to elevated temperature can override genetic sex determination, and the females can be reversed to produce pseudomales (Baroiller et al, 2009). Blue tilapia ( Oreochromis aureus ), Japanese flounder ( Paralichthys olivaceus ), European sea bass ( Dicentrarchus labrax ), turbot ( Scophthalmus maximus ) and Atlantic silverside ( Menidia menidia ) also undergo temperature induced ESR (Conover and Fleisher, 1986; Desprez and Mélard, 1998; Yamaguchi et al, 2007; Diaz and Piferrer, 2015; Robledo et al, 2015; Diaz and Piferrer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in the European sea bass showed that genes related to ovarian differentiation such as wisp1, cyp19a, and 17β-hsd and testicular differentiation such as amh, dmrt1, and tesc are downregulated after exposure to high temperature and E2 treatment. Suppression of all these genes results in the feminisation of the fish [158]. However, a contrasting report showed an increase in cyp19a gene expression following E2 treatment and suppression of cyp19a following exposure to high-temperature results in masculinisation [159].…”
Section: Sex Hormonesmentioning
confidence: 96%
“…A wide range of natural E2, synthetic oestrogen, and synthetic androgen (17α-methyltestosterone) have been used to produce monosex fish. Both types of steroids are readily metabolized post-treatment [152,158,159].…”
Section: Sex Hormonesmentioning
confidence: 99%
“…Aromatase catalyzes the conversion of androgens into estrogens, a process that is essential to sex differentiation and sex development. As a critical gene in estrogen biosynthesis, cyp19a influences gonadal differentiation processes and the population sex ratio by regulating the biosynthesis of gonadal steroid hormones in birds (Smith & Sinclair, ; Vaillant, Dorizzi, Pieau, & Richard‐Mercier, ), teleost fish (Caruso, Breton, & Berlinsky, ; Díaz & Piferrer, ), amphibians (Nakamura, ; Olmstead et al, ), and reptiles (Jeyasuria & Place, , Ramsey & Crews, ). The use of specific aromatase agonists or aromatase inhibitors can cause genetic males to display female phenotypes, and genetic females to display male phenotypes, in various vertebrate species.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the expression of cyp19a and estrogen production in the American alligator showed that cyp19a is not the initial trigger for alligator sex determination, but played a necessary role in ovarian differentiation (Gabriel, Blumberg, Sutton, Place, & Lance, ). Exposure of fish to exogenous estrogens during sexual differentiation had a profound effect on reprogramming their gonadal transcriptome, resulting not only complete feminization of the population but in inhibition of steroidogenesis in developing females (Díaz & Piferrer, ).…”
Section: Introductionmentioning
confidence: 99%